Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/bimj.202200132
|View full text |Cite
|
Sign up to set email alerts
|

Random‐effects meta‐analysis models for the odds ratio in the case of rare events under different data‐generating models: A simulation study

Abstract: This article has earned an open data badge "Reproducible Research" for making publicly available the code necessary to reproduce the reported results. The results reported in this article could fully be reproduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 58 publications
(126 reference statements)
2
12
0
Order By: Relevance
“…When meta‐analyses of rare events are based on small numbers of studies, the ML approach for the BBM may fail to converge, or it may provide biased estimates 9,10 . Bayesian estimation may be well‐suited to solve these problems, because by incorporating sensible prior information, Bayesian methods can help to stabilize parameter estimates.…”
Section: Bayesian Estimation Of the Bbmmentioning
confidence: 99%
See 4 more Smart Citations
“…When meta‐analyses of rare events are based on small numbers of studies, the ML approach for the BBM may fail to converge, or it may provide biased estimates 9,10 . Bayesian estimation may be well‐suited to solve these problems, because by incorporating sensible prior information, Bayesian methods can help to stabilize parameter estimates.…”
Section: Bayesian Estimation Of the Bbmmentioning
confidence: 99%
“…As our aim was to evaluate the performance of frequentist and Bayesian BBMs for meta‐analyses of few studies, we generated meta‐analyses with five and 10 studies. Although smaller numbers of studies are common in meta‐analyses, 14,26 simulations have shown that the performance of frequentist models is already compromised when meta‐analyses consist of only five studies 9,10 . We considered conditions with small and large sample sizes (ni=100 and ni=500, where ni is the total sample size of the ith study).…”
Section: Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations